The SYNTAX Revascularization Index and major cardiovascular events in patients with multivessel coronary artery disease in the Instituto Nacional de Cardiología Ignacio Chávez – Mexico - Vásquez Loarte, Tania (2023)
Objective. To evaluate the degree of incomplete revascularization in patients with multiarterial coronary artery disease who underwent percutaneous coronary intervention (PCI) or coronary artery bypass surgery (CABG) using the Syntax revascularization index (SRI) and its relationship to major cardiovascular events during follow-up. Materials and Methods. Observational, retrospective study with 4-year follow-up of patients with multiarterial coronary artery disease who underwent surgical or percutaneous coronary revascularization, in whom the baseline Syntax score (SSb) and the residualSyntax score (SSr) were calculated. The Syntax Revascularization Index (SRI) was determined withthe following formula: SRI = (1- [SSr/SSb]) x 100, and major cardiovascular events at 4-year follow-up were compared. Results. Two hundred patients (100 in each group) were evaluated. Mean SSr in group 1 was 83.2%, and in group 2, 79.0% (p=0.88). Mean complete revascularization was 41% in the first group and 35% in the second. A cutoff point of ≤90% of IRS had the best accuracy for predicting major cardiovascular events (area under the curve of 0.60; 95% CI: 0.49-0.71, p<0.05). In multivariate analysis IRS was an independent predictor of major cardiovascular events (HR 2.6; 95%CI: 1.32-3.22, p= 0.043). Conclusions. The Syntax Revascularization Index may be useful for measuring the degree of revascularization in patients with multiarterial coronary artery disease treated percutaneously or surgically. An SRI ≥90% may be an acceptable target for revascularization.